Methodological Background of the Assessment of Reliability of the Professional Activity of the Personnel Working with PBA of Pathogenicity Groups I-II - T. A. Malyukova; A. F. Bobrov; V. Yu. Scheblanov; L. A. Tikhomirova; A. V. Boiko; A. V. Toporkov (Проблемы особо опасных инфекций, 2010)
Considered was the actuality of investigations to assess the reliability of occupational activity of personnel authorized to work with PBA of I-II groups. The methodological approaches and assessment criteria were developed on the base of existing regulatory documents on the work safety and complex approach to personnel training.